Kuhn's theorem for extensive form Ellsberg games - Linda Sass (Bielefeld University, Institute of Mathematical Economics (IMW), 2013)
Riedel and Sass (2013) propose a framework for normal form games where players can use imprecise probabilistic devices. We extend this strategic use of objective ambiguity to extensive form games. We show that with rectangularity of Ellsberg strategies we have dynamic consistency in the sense of Kuhn (1953): rectangular Ellsberg strategies are equivalent to Ellsberg behavior strategies. We provide an example for our result and define Ellsberg equilibrium in such extensive form Ellsberg games.
urn:nbn:de:0070-pub-26740884
Keywords: C72; C73; D81; 330; knightian uncertainty in games; objective ambiguity; strategic ambiguity; extensive form Ellsberg games; Kuhn's theorem; rectangularity